Cross-cultural comparison of self-stigma in psychological help-seeking: a study of local and international university students in Malaysia - Kesantini Athinarayanan Rao; Getrude C.Ah Gang; Carmella E. Ading (Penerbit Universiti Malaysia Sabah, 2024)
In recent years, there has been an increase in mental health challenges among university students in Malaysia. Despite this, local and international students exhibit a reluctance to seek psychological help, revealing a gap in addressing mental health needs. Self-stigma emerges as a significant barrier to proactive psychological help-seeking attitudes. Cultural nuances further complicate attitudes toward seeking psychological help. To further understand the interplay between self-stigma and psychological help-seeking attitudes among different cultures and genders, a cross-cultural comparison study was conducted. Eight universities consisting of four public and four private universities in Malaysia were chosen as the sample population of this study. The instruments that were used were the Attitudes towards Professional Psychological Help-Seeking Scale -Short Form (ATSPPH-SF) and the Self-Stigma of Seeking Help (SSOSH). Results revealed that self-stigma negatively predicted psychological help-seeking attitudes among university students, particularly among international students. Furthermore, male international students were more open to seek professional psychological help while female international students placed more value and need on psychological help. Overall, the psychological help-seeking attitudes remained low and insignificant across the samples. Therefore, integrating cultural perspectives into mental health interventions may help build trust and provide supportive environments that may encourage positive psychological help-seeking attitudes.